(untitled) (The Pakistan Development Review, 1993)
Price distortions induce inefficient utilisation of resources by giving incorrect signals to producers and consumers. Since distorted prices do not reflect the real value of resources, quantities of goods and services produced may not be consistent with their demand. The price Distortions may be caused by a number of different reasons. They may, for instance, be caused by monopolistic tendencies, preferential treatment of a particular sector of economy, establishment of diffusion of a particular product or an input, etc. In fact, price distortions occur sometimes from deliberate and sometime inadvertent Government policies of subsidies and price supports in pursuance of certain social or economic objectives. Both producers and consumers maximise their economic welfare by allocating their resources in response to price signals from a fully comPetitive market. Since movements in commodity prices especially food prices affect producers and consumers in exactly the opposite way, fixation of their prices in developing countries represents a policy dilemma. While prices of all items used by consumers and .producers are iml?ortant, food prices carry a unique significance in low income countries where the marginal propensity to consume is very high. Since farm producers are also food consumers, the net impact of a food price change in their case will depend on the extent to which they have emerged from a subsistence economy. However, if inputs are subject to price fixation, the impact will be felt more readily and directly. In fact, where there is no Government intervention, prices equilibrate consumer demand with the productive capacities of producers. If prices are distorted by any agency their allocative role is seriously diminished. Imperfections of both size and operation being prevailed ultimately induce misallocation of resources in the country. Resource use efficiencies increase, if government restricts its role to ensuring proper functioning of the market and lets the prices to be determined by the forces of demand and supply.